Study Literature Review : Pengaruh Efektivitas Terapi Aktivitas Kelompok Terhadap Tingkat Depresi Pada Lansia - Vivie Alhawari; Ayu Pratiwi (Sekolah Tinggi Ilmu Kesehatan Yatsi, 2021)
Background : Elderly who experience depression by 15.9%, elderly people aged 65-74 years by 23.2%, and age over 75 years amounted to 33.7% of people with depression and only 9% of people with depression in Indonesia those who take medicine or undergo medical treatment, it is necessary to intervene to reduce the level of depression by providing positive activities and social interactions such as Group Activity Therapy. Research Objectives: Knowing the effectiveness of group activity therapy carried out by previous researchers and depictions of depression in the elderly. Research Methods : Traditional literature review, obtained from a journal, that is, reviewing, critically reviewing knowledge, ideas, and findings contained in the literature. Research Results : Group activity therapy carried out by previous researchers was very effective in reducing the level of depression in the elderly seen in the results of pre-test and post-test, which were carried out in different institutions in Indonesia. Conclusion : There is a decrease in the level of depression in the elderly after giving group activity therapy from the results of the pre-test and post test, the level of depression is influenced by various factors that greatly affect the level of depression in the elderly.